2011
DOI: 10.1021/ma2021453
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide-Induced Polyethylene Crystallization in Solution and Nanocomposites

Abstract: We report epitaxial crystallization of polyethylene (PE) on reduced graphene oxide (RGO) nanosheets via a controlled solution crystallization method. Polarized light microscopy, scanning electron microscopy, transmission electron microscopy, and atomic force microscopy were used to investigate morphology of RGO-induced PE crystals. The PE edge-on crystals formed from randomly distributed rodlike nuclei on the basal plane of RGO nanosheets and further grew into larger lamellae with an average dimension of a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
119
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(138 citation statements)
references
References 47 publications
15
119
2
2
Order By: Relevance
“…Cheng et al reported a strong nucleation effect of reduced graphene oxide (rGO) and polyethylene nanocomposites. Contrary to our results, the authors observed a decrease in the value of n, but this decrease was attributed to the growth of numerous spherulites at or near the rGO surface, which impinge with each other at early stages of crystallization and form a quasi-2D layer of spherulites [25]. Similarly, the nucleation effect of graphene and functionalized graphene has been reported for many other polymers, e.g., polypropylene [34,35] and polyphenylene sulfide [36].…”
Section: Crystallization Kineticscontrasting
confidence: 99%
See 1 more Smart Citation
“…Cheng et al reported a strong nucleation effect of reduced graphene oxide (rGO) and polyethylene nanocomposites. Contrary to our results, the authors observed a decrease in the value of n, but this decrease was attributed to the growth of numerous spherulites at or near the rGO surface, which impinge with each other at early stages of crystallization and form a quasi-2D layer of spherulites [25]. Similarly, the nucleation effect of graphene and functionalized graphene has been reported for many other polymers, e.g., polypropylene [34,35] and polyphenylene sulfide [36].…”
Section: Crystallization Kineticscontrasting
confidence: 99%
“…The insignificant change in the crystalline melting temperature indicates that the reduction in crystallinity may be due to restriction of chain movements by graphene. Shan et al also reported insignificant changes in T m for reduced graphene oxide and polyethylene nanocomposites [25]. The chain heterogeneity and microstructure can be analyzed by CRYSTAF.…”
Section: Crystallinity and Microstructure Analysismentioning
confidence: 99%
“…The orientation of crystals in PCL/RGO nanocomposites obviously enhances, and its mechanical property significantly improves. Analogously, another high crystallization polyethylene (PE) can epitaxially grow on the interface of laminated RGO and the mechanical properties of PE/RGO nanocomposite were improved [33,34]. However, the influence of epitaxial crystallization in a semi-crystalline polymer with H-bond and RGO nanocomposites is rarely mentioned in industrial production modeling.…”
Section: Introductionmentioning
confidence: 99%
“…For a solid-liquid PCM utilizing crystallization-melting, the latent heat depends on the crystallinity of the active material. The crystallization of a matrix material can be accelerated by the presence of heterogeneous fillers because of their nucleating effect [36]. Whereas the structural characteristics of the fillers or the strong interactions between the fillers and the matrix material at the interface can inhibit the crystallization of the matrix material [37,38].…”
Section: Resultsmentioning
confidence: 99%